Results of conjunctival autograft in pterygium surgery in Lumbini Eye Instititue, Nepal - Dhakhwa, K; Patel, S; Sharma, MK; Rai, SKC; Bhari, AM (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: A pterygium is a wedge shaped fibrovascular growth of conjunctiva that extends onto the cornea. Various surgical techniques are used to treat this condition. Conjunctival graft over the bare sclera is one of the techniques used. The present study was done to evaluate the efficacy of autologous conjunctival graft in surgical management of primary and recurrent pterygium. MATERIALS AND METHODS: All the patients who underwent conjunctival autograft surgery for primary and recurrentpterygium from 1st Jan. 2010 to 30th June 2010 were enrolled prospectively. Follow up was done for six months after the surgery. RESULTS: A total of240 patients operated for primary and recurrent pterygium were enrolled in this study. There were 107 (44.6%) male and 133 (55.4%) female with male to female ratio 1: 1.3. Patients' age ranged from 15 to 80 years. Recurrences occurred in 3 ( 1.25%) cases. CONCLUSIONS: Free conjunctival autograft is a safe and effective procedure for prevention of recurrence in pterygium surgery. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10482 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 2-6